Long-Term Evaluation of a Selective Retrograde Coronary Venous Perfusion Model in Pigs (Sus Scrofa Domestica) - Harig, Frank (American Association for Laboratory Animal Science, 2011)
The lack of suitable target vessels remains a challenge for aortocoronary bypass grafting in end-stage coronary heart disease. This study aimed to investigate the arterialization of cardiac veins as an alternative myocardial revascularization strategy in an experimental long-term model in pigs. Selective retrograde perfusion of a coronary vein (aorta to coronary vein bypass, retrobypass) before ligation of the ramus interventricularis paraconalis (equivalent to the left anterior descending artery in humans) was performed in 20 German Landrace pigs (Sus scrofa domestica). Retroperfusion of the left anterior descending vein was performed in 10 pigs (RP+) but not in the other 10 (RP–), and the vena cordis magna was ligated (L+) in 5 pigs in each of these groups but left open (L–) in the remaining animals. Hemodynamic performance (for example, cardiac output) was significantly better in the group that underwent selective retroperfusion with proximal ligation of vena cordis magna (RP+L+; 4.1 L/min) compared with the other groups (RP+L–, 2.5 L/min; RP–L+, 2.2 L/min; RP–L–, 1.9 L/min). Long-term survival was significantly better in RP+L+ pigs (112 ± 16 d) than in all other groups. Histologic follow-up studies showed significantly less necrosis in the RP+L+ group compared with all other groups. Venous retroperfusion is an effective technique to achieve long-term survival after acute occlusion of the left anterior descending artery in a pig model. In this model, proximal ligation of vena cordis magna is essential.